Editorial Special Section on Invited Papers in 2021 on Emerging Topics in the Power and Energy Society - Fangxing Fran Li (IEEE, 2021)
The publication of the 2020 Special Section of Invited Papers on Emerging Topics in the Power and Energy Society (PES) received broad interest from diverse readers of the PES community. We continued to publish the special section for another year. After a rigorous peer-review process, a total of 13 papers [A1]–[A13] were accepted for publication in this invited section of the IEEE Open Access Journal of Power and Energy (OAJPE) in 2021.